DC motor drives using Peripheral Interface Controller (PIC): article - Jasni, Khairul Fitrie (2010)
Direct current (DC) motor has already become an important drive configuration for many applications across a wide range of powers and speeds. The case of control and excellent performance of the DC motors will ensure that the number of applications using them will continue grow for the foreseeable future. This project is mainly concerned on DC motor speed control system by using microcontroller PIC 16F877A. It is a closed-loop real time control system, and provides the feedback speed signal to controller. Pulse Width Modulation (PWM) technique is used where its signal is generated in microcontroller. Through the project, PI controller is implemented into PIC using C program language. In microcontroller, it will calculate the error between the desired speed with the actual speed. The error will determine duty cycle of pulse-width- modulation (PWM) in microcontroller. Then, the duty cycle will send to DC motor driver either accelerate or decelerate DC motor to maintain it at desired speed.